The effect of variation of soil and humidity to ground penetrating radar imaging analysis - Nor Liyana Mansor, 1991-, author; Shaharuddin Mohd. Said, supervisor; Fakulti Geoinformasi dan Harta Tanah (2014)
Project Paper (Sarjana Muda Kejuruteraan (Geomatik)) - Universiti Teknologi Malaysia, 2014